Impact of transit-time flow measurement on early postoperative outcomes in total arterial coronary revascularization with internal thoracic arteries: a propensity score analysis on 910 patients. (3rd March 2022) - Laali, Mojgan; Nardone, Nathalie; Demondion, Pierre; D'Alessandro, Cosimo; Guedeney, Paul; Barreda, Eleodoro; Lebreton, Guillaume; Leprince, Pascal
Abstract: OBJECTIVES: The aim of this study was to evaluate the impact of transit-time flow measurement (TTFM) on early postoperative outcomes in total arterial coronary revascularization. METHODS: A single-centre retrospective analysis was conducted on 910 patients undergoing isolated total arterial coronary artery bypass grafting with internal thoracic arteries (ITAs) at our institution, between January 2017 and February 2020. Complete arterial revascularization with bilateral ITAs with a Y-configuration, or single ITA, was planned for all patients. According to the surgeon preference, TTFM was assessed in 430 patients (TTFM group). They were compared with 480 patients without TTFM assessment (no TTFM group). Primary end point was the occurrence of in-hospital major cardiac adverse events (MACE). A propensity score analysis with an inverse probability weighting approach was performed to control for selection bias. RESULTS: TTFM was associated with longer cardiopulmonary bypass times (76.0 [62.0; 91.2] vs 79.0 [65.0; 94.0] min, P = 0.042). Six (1.4%) patients in the TTFM group versus no patient in the no TTFM group underwent intraoperative graft revision because of unsatisfying flow values ( P = 0.011). MACE were significantly lower in the TTFM group (14, 3.3%) than in the no TTFM group (33, 6.9%, P = 0.014). At crude regression, TTFM was protective against MACE occurrence (odds ratios 0.46, 95% confidence interval 0.23–0.85, P = 0.016). Inverse probability weighting adjustment did not significantly displace P -values and odds ratios for MACE occurrence in the TTFM group 0.44, 95% confidence interval 0.28–0.69, P < 0.001. CONCLUSIONS: Even if associated with longer cardiopulmonary bypass times, intraoperative graft flow measurement with TTFM reduces MACE occurrence and it should be recommended for graft evaluation in arterial coronary artery bypass grafting surgery. Abstract : Since the first coronary artery bypass grafting (CABG) surgery over 5 decades ago, reducing perioperative adverse events and improving graft patency have obsessed surgeons.